2015
DOI: 10.3109/09637486.2015.1007452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant capacity of Chinese five-spice ingredients

Abstract: Phenolic compounds in spices were reportedly found to possess high antioxidant capacities (AOCs), which may prevent or reduce risk of human diseases such as cardiovascular disease, cancer and diabetes. The potential AOC of Chinese five-spice powder (consist of Szechuan pepper, fennel seed, cinnamon, star anise and clove) with varying proportion of individual spice ingredients was investigated through four standard methods. Our results suggest that clove is the major contributor to the AOC of the five-spice pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
8
1
1
Order By: Relevance
“…According to studies of Bi et al. (), the strong correlation between TPC and AC measured by ABTS was observed for cloves extracts. It may suggest that active compounds from cloves have high contribution to antioxidant overall capacity of RBC.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…According to studies of Bi et al. (), the strong correlation between TPC and AC measured by ABTS was observed for cloves extracts. It may suggest that active compounds from cloves have high contribution to antioxidant overall capacity of RBC.…”
Section: Resultsmentioning
confidence: 85%
“…The strong correlation between TPC/ABTS and TPC/PCL ACW data (r = 0.97 and r = 0.81, respectively) were observed. According to studies of Bi et al (2015), the strong correlation between TPC and AC measured by ABTS was observed for cloves extracts. It may suggest that active compounds from cloves have high contribution to antioxidant overall capacity of RBC.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Fruit with high antioxidants implies high nutritional value. DPPH and ABTS radical systems were extensively used to measure antioxidant capacity of various antioxidant compounds (Bi, Soong, Lim, & Henry, ; Feng et al, ). Results in the present work showed that DPPH and ABTS radical‐scavenging activities were induced by precooling treatment and reached max on the 15th day of storage, which suggested the precooling treatment had potential effect to enhance the nutritional value of fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have displayed that the use of antioxidants, as well as herbal agents, might help to reduce OS. 9 Furthermore, medicinal herbs are expected to have a similar degree of efficacy without the side effects related to conventional medication.…”
Section: Introductionmentioning
confidence: 99%